The effect of physical effort on the performance of some special motor abilities and the level of performance of the scoring skill of football players (Journal of the College of Basic Education, 2022)
Physical effort affects the internal organs of the football player during training or the match and as a result many internal changes occur in the functions of these devices such as the circulatory system, the respiratory system and the nervous system. High without dropping the level, as this decrease in the level is inevitable, but the efficiency of performance must be maintained as much as possible, and through the researcher’s follow-up and practice of the game of football, he noticed that there is a weakness in the performance of the skill of scoring on the goal, especially in the middle and in the last minutes of the match, as this The weakness came as a result of a decrease in the level of performance of motor abilities, because this skill needs accuracy in performance, as maintaining the efficiency of physical and motor abilities throughout the match period is of great importance, as the decrease in motor abilities affects the performance of basic skills, including the scoring skill, as the player maintains a level His performance of the scoring skill is one of the important steps to achieve victory in the match, so the researcher decided to study this problem and put The appropriate solutions for it, and the research aims to identify the results of the performance tests of some motor abilities and test the accuracy of scoring before and after the performance of physical effort, The researcher used the descriptive approach in the survey method for its suitability to the nature of the research problem and the research sample consisted of the players of Al-Fahd Football Club, which amounted to (14) players, and they represented a ratio of (63.63). Scoring was affected by the physical effort test used. The researcher recommends the necessity of linking the motor and skill abilities of the players to take advantage of the players’ skills for the longest possible period during the match, and for the coaches to rely on the implementation of training for the skill of scoring under conditions similar to the match through physical effort and training loads that the players are exposed to during training and to develop special motor abilities such as compatibility Agility, accuracy and others